A new multidimensional model of writing for research publication: An analysis of disciplinarity, intra-textual variation, and L1 versus LX expert writing. Issue 53 (September 2021) - Omidian, Taha; Siyanova-Chanturia, Anna; Biber, Douglas
Abstract: Scholarly knowledge in contemporary academia is created and communicated primarily through writing for research publication. It is through this particular form of knowledge dissemination that a rich body of scientific knowledge about a given phenomenon is accumulated. The present study sought to investigate the linguistic characteristics of knowledge communication in research writing from multiple perspectives. For this purpose, a multivariate approach was adopted to develop a new multidimensional model of research writing based on three key factors: disciplinarity, intra-textual variation, and L1 versus LX expert writing. Our analysis revealed three fundamental linguistic dimensions underlying discourse practices in research writing. Our results showed that the identified dimensions have the potential to provide detailed descriptions of linguistic relations among main sections of research articles. It was also found that the linguistic co-occurrence patterns defining these functional dimensions can be strongly affected by disciplinary preferences, and that any characterization of research writing with no careful consideration given to such factors would be incomplete. Our findings further revealed considerable differences between L1 and LX expert writing in fulfilling the communicative practices related to the evaluation and elaboration of research findings.